Historical Perspectives on Property and Land Law. An Interdisciplinary Dialogue on Methods and Research Approaches - Fiocchi Malaspina, Elisabetta (ed.) (Historia del Derecho, 2019)
This volume aims to investigate, with an interdisciplinary approach, how legal property regimes, land law and land registration systems are intertwined with economic, social, and political spheres; to analyse the social functions and legal and political implications of various land registration systems in different contexts and how, for example, they operated in a colonial framework; to scrutinise the relations between politics and property, as well as the transformation of the property concept, in its meaning and function.